PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD NEGERI 20 PEKANBARU - Pramita, Yulia Dewi; Alim, Jesi Alexander; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis research was conducted from many flat-rate yields low student learning math with the number of students who do not complete the 18 students 60% whereas the categories has been completed totalling 12 students 40%. The purpose of this research is to improve the results of learning mathematics by applying cooperative learning model type to Make A Match. Then the researcher formulates the following problems, whether the application of the cooperative learning model types Make A Match can improve student learning outcomes grade IV SD Negeri 20 Pekanbaru? This research method using class action Research, this research was conducted two cycles with each cycle two times and one time repeats daily. This research involves students grade IV SD Negeri 20 Pekanbaru as many as 30 students. This action was carried out from September to October 2013. The results obtained from studied mathematics initial data with an average 59,27 categories – less with a minimum of 65 ketuntasan with standard KKM. In cycle I, UH I mean – median results obtained studying mathematics category 64,67 enough, next on cycle II study results increased the UH II back into a category well. 80,13 Research results on the first cycle, a teacher at the time the learning process less understood type of cooperative methods Make A Match so it is difficult to apply them. But in the second cycle, the methods of cooperative types Make A Match of it can be applied to the maximum. It is characterized by a large number of students who complete a math lesson in this. Summary of the study is a model of cooperative types Make A Match has been successfully applied optimally in the results of learning mathematics school classrooms IV SD 20 Negeri Pekanbaru.Key words: Cooperative Learning types Make A Match, the result of learning Mathematics